Realizacja programu reprywatyzacji w Polscew latach 1989–2001 (aspekt polityczny i ideologiczny) - Patkowski, Krzysztof (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2004)
Reprivatization is one of the problems Polish politicians have failed to solve for 15 years. They developed nearly a score of drafts of reprivatization acts, none of which has been implemented. Election campaigns and government changes most frequently obstructed them. This happened to the draft developed by Hanna Suchocka’s government, later withheld by the next government of Waldemar Pawlak and the coalition of SLD-PSL (Democratic Left Alliance – Polish People’s Party). The coalition AWS-UW (Solidarity Election Action – Freedom Union) was very likely to launch reprivatization. Although it had the required majority in the Parliament, the political disputes inside the Solidarity Election Action prevented reprivatization. For the Solidarity Election Action with Marian Krzaklewski, general endowment was to ensure the victory to the party and himself in the next parliamentary and presidential elections respectively. As a result of the internal disputes, the reprivatization act was vetoed by President Kwaśniewski and the elections marked the AWS’s collapse. After Poland’s accession to the European Union former property owners have increasingly been demanding to restore the seized property, yet the issue does not seem likely to be solved soon and the very idea of reprivatization dissolves in political and ideological controversies.
Implementation of the Reprivatization Process in Poland in 1989-2001 (political and Ideologica Aspect)